The Role of E-Service and Food Quality to Users Satisfaction of Online Food Delivery Service in Surabaya - Kristy, Jovanka; Novika, Fitri; Kusumawardhany, Prita Ayu (Program MM Universitas Surabaya, 2026)
Purpose: This study aims to examine the effect of perceived control, service convenience, customer service, service fulfillment, food quality on customer satisfaction and customer satisfaction on behavioral intentions in online food delivery service users. Method: Respondents in this study were users of online food delivery services in Surabaya. The data taken for this study were 200 respondents in Surabaya who had made transactions more than 2 times in the last 3 months on the online food delivery service provider application and respondents who had used the customer service feature. The data that has been collected is then analyzed with the Structural Equation Modeling (SEM) measurement model using IBM SPSS version 24 and Smart PLS 4 software. Result: After the data processing process, the results show that the perceived control variable does not have a significant effect on customer satisfaction. Meanwhile, the variables of service convenience, customer service, service fulfillment, and food quality have a positive and significant effect on customer satisfaction and the variable customer satisfaction has a positive and significant effect on behavioral intentions in online food delivery service users in Surabaya.